'You are safe. You are not alone:' gender and Social Support Coping (SSC) in public safety personnel. Issue 4 (19th May 2023) - Kaur, Navjotpal; Ricciardelli, Rosemary; Fletcher, Amber; Carleton, R. Nicholas
ABSTRACT: Public Safety Personnel (PSP) experience significant job-related stressors including potentially psychologically traumatic event (PPTE) exposures that may compromise mental health; as such, strategies are needed to mitigate the impact of stressors. Substantial research evidence indicates that social support is a crucial strategy for enhancing mental health and well-being in PSP and non-PSP populations alike. Gender differences in using social support are understudied among PSP and stereotypical gender attitudes appear highly prevalent in PSP occupations. In the present study, we explore the differential use of social support by men and women PSP; specifically, personal, informal, and formal social support. We analyse 137 responses to two open-ended questions regarding Social Support Coping (SSC) from participants obtained through an online self-report survey for PSP. Our results suggest that gender significantly impacts how men and women PSP seek help or support from their peers, spouses, friends, or supervisors. Men appeared to rely more on families or spouses, whereas women sought support from friend groups or relationships based on reciprocity and formal programmes.